Bio-distribution of Gold Nanoparticles in Tumor Mass and Different Organs in Implanted Mice with Mammary Adenocarcinoma AM3 (in vivo study) - Hussein, Sumaiah I; Shubber, Saleha S.; Yaseen, Nahi Y . (The Iraqi Journal of Veterinary Medicine, 2019)
Nanoparticles has many properties, especially in treatment of medical field, but the controversy continues about their cytotoxicity. Hence, this research was conducted to estimate the concentration of gold nanoparticles (GNPs) in tumor and other organs such as kidney, liver, and spleen after injection GNPs by two routes, intratumor and intraperitoneal to compare between two methods in mice implanted with mammary adenocarcinoma for 28 days. Atomic Absorption Spectroscopy was used to measure the GNPs concentrations. The results revealed that the GNPs concentrations were significantly (P≤0.05) increased (3.75±1.75, 2.42 ±0.31 ppm) in kidney tissue after intratumor and intraperitoneal administration, respectively, when compared to the other organs (liver and spleen), followed by tumor mass (2.66±0.01, 1.09 ±0.06 ppm) in tissue. While the concentrations of GNPs in spleen and liver were (1.40 ±0.33, 0.726 ±0.01) and (0.602 ±0.03, 0.517 ±0.02) after intratumor and intraperitoneal administration respectively. Also, the experiment showed that the injection by intratumor was more efficient than intraperitonial method for tumor treatment, so, the nanoparticles were cleared by responsible lymphoid organs of body.